2021
DOI: 10.3390/brainsci11081078
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Guided Transcranial Electrical Stimulation in Enhancing Surgical Skill Acquisition. Comment on Hung et al. The Efficacy of Transcranial Direct Current Stimulation in Enhancing Surgical Skill Acquisition: A Preliminary Meta-Analysis of Randomized Controlled Trials. Brain Sci. 2021, 11, 707

Abstract: Surgical skill acquisition may be facilitated with a safe application of transcranial direct current stimulation (tDCS). A preliminary meta-analysis of randomized control trials showed that tDCS was associated with significantly better improvement in surgical performance than the sham control; however, meta-analysis does not address the mechanistic understanding. It is known from skill learning studies that the hierarchy of cognitive control shows a rostrocaudal axis in the frontal lobe where a shift from post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In contrast, the fMRI studies showed additional activation of deeper brain structures, including the basal ganglia and cerebellum [80]. Future studies need to apply the perceptionaction system based on brain-behavior analysis during a learning curve study [25], where the chain of mental processes can depend on the task complexity [100], 707).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the fMRI studies showed additional activation of deeper brain structures, including the basal ganglia and cerebellum [80]. Future studies need to apply the perceptionaction system based on brain-behavior analysis during a learning curve study [25], where the chain of mental processes can depend on the task complexity [100], 707).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results of this study are conducive to the exploration of transcranial electrical stimulation 113 to facilitate learnability in medical simulators. For example, mobile brain-behavior analysis with fNIRS can capture the interaction between the angular gyrus (AG) and the middle frontal gyrus (MFG) that is underpinned by the dorsal superior longitudinal fascicle (SLF II) 114 , and the subjective sense of agency may be facilitated by neuroimaging-guided transcranial electrical stimulation 113 of the AG-MFG interactions 115 . The dorsal branch of the superior longitudinal fasciculus, which is responsible for visuospatial integration and motor planning, is linked to lateralized hand preference and manual specialization 116 .…”
Section: Discussionmentioning
confidence: 97%
“…Here, the premotor and motor areas were combined in the PMC (see Table S1), and the fNIRS optode montage could not distinguish the SMA proper from the preSMA brain regions, which may be important to better assess the temporal structure 124 of the perception-action coupling link 70 . Additionally, we did not investigate all of the subregions of the PFC, e.g., the ventrolateral PFC and inferior frontal gyrus (IFG), that may have essential functional interactions during FLS surgical skill acquisition 113 , where the feasibility of fNIRS' temporal resolution needs to be demonstrated in the future to capture the fast interactions that are expected via shorter frontal lobe connections 119 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations